given: $z^2 + 0.8 \sqrt2 z + 0.64 = 0 $

Then, I am using the quadratic equation:

$ z_{1,2} = \frac{-0.8 \sqrt2 \pm \sqrt{(0.8\sqrt2)^2-4 \cdot 0.64}}{2} $

Wolfram Alpha says it the end there should be: $-0.4 \sqrt2 \pm j 0.4 \sqrt2$, but I get something different:

$$ = \frac{-0.8\sqrt2\pm0.8\sqrt2-2\cdot0.8j}{2} $$ $$ = -0.4\sqrt2\pm0.4\sqrt2-1.6j$$


You seem to be computing, on the square root side, something like, $a$ and $b$ being positive, $\sqrt{a-b}=\sqrt{a}-j\sqrt{b}$, which is wrong. The square root is not linear.

Here, the discriminant $\Delta = (0.8\sqrt{2})^2-4\times 0.8^2 = -2\times 0.8^2$ is negative. Hence, the roots are:

$$ z_r= \frac{-0.8\sqrt{2}\pm j\sqrt{-\Delta}}{2} = 0.4\sqrt{2}(-1 \pm j)$$

agreeing with Wolfram Alpha.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.